2017
DOI: 10.1186/s40854-017-0066-9
|View full text |Cite
|
Sign up to set email alerts
|

The volatility of returns from commodity futures: evidence from India

Abstract: Background: This paper examines the pattern of the volatility of the daily return of select commodity futures in India and explores the extent to which the select commodity futures satisfy the Samuelson hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Sehgal et al (2012) also tested the function of price discovery in the agricultural commodity markets in India and observed that price discovery exists in all commodities barring turmeric. This result is supported by Mukherjee and Goswami (2017) but in case of potato. Although a large number of researchers have opined that the futures market discovers spot prices, their results have been countered by other researchers who have found no evidence of the futures market predicting the spot price.…”
Section: Literature Surveysupporting
confidence: 61%
“…Sehgal et al (2012) also tested the function of price discovery in the agricultural commodity markets in India and observed that price discovery exists in all commodities barring turmeric. This result is supported by Mukherjee and Goswami (2017) but in case of potato. Although a large number of researchers have opined that the futures market discovers spot prices, their results have been countered by other researchers who have found no evidence of the futures market predicting the spot price.…”
Section: Literature Surveysupporting
confidence: 61%
“…On the contrary, some other studies suggest that derivatives promote increased activity on spot markets and facilitate the price discovery process (Chakravarty et al , 2004). Thus, the efficiency of derivative markets, particularly commodity futures markets, have become more sophisticated nowadays (Mukherjee and Goswami, 2017).…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…In a comprehensive study to understand the dynamics of the co-integration, price causality and volatility factors, which determine the efficiency of commodity markets, Mukherjee and Goswami (2017) reveal that futures market; lead the spot market in India. In terms of volatility, the GARCH test results convey that there are volatility clustering and persistence throughout the study period.…”
Section: Literaturementioning
confidence: 99%
“…(Manera et al, 2013) the study served the return volatility of selected commodity as financial assets i.e., gold, potato, Mentha oil and crude oil traded under MCX (multi commodity exchange), India covering the period from 2004 to 2012 by using GARCH Model. (Mukherjee and Goswami, 2017) investigated the prediction capability of GARCH, GJR-GARCH, EGARCH and APARCH models together with the different error constructs like Student's t-distribution, normal distribution and asymmetric Student's t-distribution with a comparison between asymmetric and symmetric distributions using these three different error constructs by taking two major indices of Tel-Aviv stock exchange (TASE) i.e., TA25 and TA100. The results suggest that overall estimation can be improved by employing the asymmetric GARCH model with fat-tailed densities for estimating conditional variance (Alberg et al, 2008).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The residual terms should be conditionally normally distributed and serially uncorrelated." (Mukherjee and Goswami, 2017) One of the major limitations of this ARCH model is it "supposes that the variance or heteroscedastic of tomorrow's return is an equally-weighted average of the residuals' squared from the last 22 days. The assumption of equal weights looks ill-favoured, as one may think that the more recent events would be more significant and therefore should have more weights" (Engle, 2001).…”
Section: Introductionmentioning
confidence: 99%